Dose equivalence and bronchoprotective effects of salmeterol and salbutamol in asthma. Issue 11 (November 1997) - Higham, M A; Sharara, A M; Wilson, P; Jenkins, R J; Glendenning, G A; Ind, P W
Abstract : BACKGROUND: Salbutamol is the most widely prescribed short acting beta 2 agonist and salmeterol is the first long acting inhaled beta 2 agonist. The dose equivalence of salmeterol and salbutamol is disputed. Estimates of weight-for-weight dose ratio have ranged from 1:2 to 1:16. A study was undertaken to clarify the true dose ratio. METHODS: The bronchoprotection afforded against repeated methacholine challenge by inhaled salmeterol 25 micrograms and 100 micrograms and salbutamol 100 micrograms and 400 micrograms was compared in a randomised, double blind, placebo controlled, crossover trial. Subjects were 16 stable asthmatics with a baseline forced expiratory volume in one second (FEV1) of > or = 65% predicted, screening concentration provoking a fall in FEV1 of 20% (PC20FEV1) of < or = 8mg/ml, and a shift in PC20FEV1 of more than two doubling concentration steps following inhalation of salbutamol 400 micrograms. On five separate occasions subjects underwent methacholine challenge before and 30 and 120 minutes after drug administration. PD20FEV1 was calculated for each challenge. FEV1 at 90 minutes after drug administration was also recorded. RESULTS: Bronchoprotection afforded by salmeterol was increased at 120 minutes compared with 30 minutes and protection by salbutamol was decreased. Protection by both doses of salmeterol was similar to salbutamol 100 micrograms at 30 minutes but significantly greater at 120 minutes. FEV1 at 90 minutes was significantly greater after salmeterol 100 micrograms than after placebo, but there were no other significant differences between treatments. Maximal observed protection was equivalent for salmeterol 100 micrograms and salbutamol 400 micrograms. CONCLUSIONS: The data are compatible with a weight-for-weight dose ratio for salmeterol:salbutamol of < or = 1:4.